2022
DOI: 10.1186/s13017-022-00436-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the successful conservative management of nonocclusive mesenteric ischemia

Abstract: Background The criteria for deciding upon non-operative management for nonocclusive mesenteric ischemia (NOMI) are poorly defined. The aim of this study is to determine the prognostic factors for survival in conservative treatment of NOMI. Methods Patients with bowel ischemia were identified by searching for “ICD-10 code K550” in the Diagnosis Procedure Combination database between June 2015 and May 2020. A total of 457 patients were extracted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Toda et al . 30 reported that a SOFA score less than 3 and several biological markers (serum levels of albumin, total bilirubin, lactate dehydrogenase, and C-reactive protein) may help determine a treatment plan for NOMI and avoid unnecessary laparotomies. In our study, 11 patients with a SOFA score less than 3 underwent exploratory laparotomies, and all required surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Toda et al . 30 reported that a SOFA score less than 3 and several biological markers (serum levels of albumin, total bilirubin, lactate dehydrogenase, and C-reactive protein) may help determine a treatment plan for NOMI and avoid unnecessary laparotomies. In our study, 11 patients with a SOFA score less than 3 underwent exploratory laparotomies, and all required surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the pneumoperitoneum improved with careful follow-up without surgery. No reports have indicated the criteria for selecting between conservative and surgical treatment for pneumoperitoneum; however, a low sequential organ failure assessment (SOFA) score (≤ 3 points) is reportedly a useful indicator for conservative treatment in NOMI cases [ 10 ]. In our case, although it is unclear whether the pneumoperitoneum was due to NOMI, the SOFA score was 1 point, indicating that conservative treatment was appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further study is needed. Fourth, the quick Sepsis-related Organ Failure Assessment (qSOFA) score, with a cutoff value ≤ 3, was found to be a reliable predictor of survival in NOMI patients treated with conservative management[ 33 ]. We did not analyze the qSOFA score in the present work, and further study of the prognostic value of the qSOFA score in NOMI patients treated with surgery is needed.…”
Section: Discussionmentioning
confidence: 99%